The Sixth man : constructing nationalism through the news accounts of the Gilas Pilipinas National Basketball Team in international competition - KISON, KEVIN NICCOLO (Archīum Ateneo, 2017)
This study used Framing Theory to determine how the media frames the Gilas Pilipinas National Basketball team as a symbol of Philippine nationalism. A total of 100 news articles about the participation of Gilas Pilipinas in four FIBA tournaments from two of the country's most prominent broadsheets, the Philippine Daily Inquirer and Philippine Star, were analyzed to see the media's approach in promoting perceptions of nationalism for the audience. It utilized critical discourse analysis to examine the terms and angles used by the media in the news articles selected to relate the team to nationalism. This study found that the media packaged Gilas Pilipinas as a symbol for Philippine nationalism through words and themes in news articles that highlight the team's connection to the display of national pride.